Analysis of the relationship between weather conditions and air quality in the cities of Kazakhstan over an 11-year period (2010-2020) as the basis of epidemiological risks - Смагулов, Н.К.; Конкабаева, А.Е.; Тыкежанова, Г.М.; Садыкова, А.Ж.; Мукашева, Г.Ж.; Серік, А.Т. (Fundamental and Experimental Biology, 2023)
In this study, a retrospective analysis of the relationship between weather conditions and the presence of pollutants in the airspace of the city of Karaganda and Petropavlovsk for an 11-year period (2010-2020) was carried out. The dynamics of the air pollution code of the studied cities indicated a higher level of air pollution in the city of Karaganda throughout all seasons, compared with the indicators of the city of Petropavlovsk. Substances belonging to the first hazard category significantly prevailed in gaseous emissions in the city of Karaganda: nitrogen dioxide in winter, ozone in spring and summer. Phenols and formaldehyde were present in the air of Karaganda during all seasons, significantly exceeding the MPC. An analysis of the correlations between weather and environmental factors made it possible to find medium and weak direct and inverse correlations between atmospheric pollution, weather conditions and seasons. It was found that in the winter season, synergism could manifest itself due to the simultaneous presence of nitrogen dioxide and formaldehydes, the content of which in the atmosphere significantly exceeded the MPC. In the summer season, synergy could be expected due to the simultaneous presence of high concentrations of ozone and formaldehyde in the air. The complex impact of weather conditions, the level and nature of air pollution in the Karaganda region compared to the city of Petropavlovsk indicates the likelihood of a significant increase or modification of negative consequences for human health.